PRD de partido de oposición a partido de gobierno. (1989 – 2001) - Ortiz Rodríguez, Arturo (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
In selecting the research topic, which is presented as thesis, and titled: PRD from opposition party to government party (1989-2001), was projected as an analysis, directly related to the political history of Mexico today , With the purpose of studying the origins, progress and progress of the Mexican political system, during the study stage. This system has as antecedent the historical, cultural and economic problems that formed the relations, as well as the forms of political competition, before a circuit of power and dominion of the hegemonic party in the political sphere, and that date for the present case, of the When the political institutions of the Mexican State were strengthened during the presidency of General Lázaro Cárdenas. A period that historically intertwines with the institutionality of the State throughout the second half of the twentieth century. That inheritance of institutions, structures and political forms of cardenism, which permeated nationalist politics, defending the country's sovereignty, social reforms - which impacted mainly the large dispossessed population -, large popular mobilizations - corporatism - and A vision of Mexico's endogenous economic growth, which led, among other things, to the nationalization of oil in March 1938, were the historical roots of neo-cardenism of the eighties and early twenty-first century. Where the engineer Cuauhtémoc Cárdenas - son of General Lázaro Cárdenas - has become the main bearer of that political movement for the country's democracy, through the Party of the Democratic Revolution (PRD), which, over the years , He became his "moral leader"

Al seleccionar el tema de investigación -que es presentada como tesis-, y que se tituló: PRD de partido de oposición a partido de gobierno (1989 – 2001), fue proyectado como un análisis, relacionado directamente con la Historia política del México de hoy, con la finalidad de estudiar los orígenes, avance y progreso del sistema político mexicano, durante la etapa de estudio. Sistema que tiene como antecedente los problemas históricos, culturales y económicos que conformaron las relaciones, así como las formas de competencia política, ante un circuito de poder y dominio del partido hegemónico en la esfera política, y que datan para el presente caso, de los años cuarenta, cuando fueron fortalecidas las instituciones políticas del Estado Mexicano, durante la presidencia del general Lázaro Cárdenas. Época que se engarza históricamente con la institucionalidad del Estado a lo largo de la segunda mitad del siglo XX. Aquella herencia de instituciones, estructuras y formas políticas del cardenismo, que permearon la política nacionalista, de defensa de la soberanía del país, de reformas sociales –que impactaron sobre todo a la gran población desposeída-, de grandes movilizaciones populares –corporativismo- y de una visión de crecimiento económico endógeno de México, que llevó entre otras cosas a la nacionalización del petróleo en marzo de 1938, fueron las raíces históricas del neo cardenismo de los años ochenta y de principio de siglo XXI. Donde el ingeniero Cuauhtémoc Cárdenas –hijo del general Lázaro Cárdenas-, se ha convertido en el abanderado principal de ese movimiento político por la democracia del país, a través del Partido de la Revolución Democrática (PRD), del cual, al paso de los años, se fue convirtiendo en su “líder moral”.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; FH-M-2006-0007; Opción en historia regional continental; Sistema político; Michoacán; Gobierno; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/236